Study of Making Potassium Posphate from Seaweed Industrial Wastewater - Pujiastuti, Caecilia; Sumada, Ketut; Ngatilah, Yustina; Widya P, Vika; Arief S, Purwanto (Future Science)
Seaweed industrial wastewater which contains 17.9% potassium can be used as a raw material for making multi-nutrient fertilizers. 1 liter of wastewater is reacted with 1 N phosphoric acid with a certain volume (15, 20, 25, 30, 35 ml) and 30 ml of aluminum sulfate (17,18,19,20,21%) stirred at a speed of 35 rpm for 25 minutes. The precipitate formed is dried. The results showed that the greater the volume of acid and the concentration of aluminum sulfate added with fertilizer obtained and the K, P, and S ion content was getting smaller. Fertilizer produced with the highest content of K ions (9.3%), P ions (9.7%), and S (9.295%) was obtained in the addition of 17% Aluminum Sulfate coagulant and 15 ml volume of H3PO4 (1N), and fertilizers produced weighing 4.0128 grams.